Properties of fired bodies made from Tanzanian talc-clay mixes for ceramic applications. - Lugwisha, E. H. J. (Tanzania Journal of Science, 2021)
Fired properties of talc-clay mixed bodies of different compositions were investigated for ceramic applications. Clays from Pugu and Malangali and talcs from two different sites in Kikombo deposits in Dodoma Region were used. Chemical analyses, X-ray analysis and Differential Thermal analysis for clays and talcs were used for the characterisation. Moulded mixed samples of clay and talc dried at room temperature at 1100C for 24 hours were fired at 1200, 1250, 1300 and 13500C for 6 hours. Both clay deposits consist mainly of kaolin. Talc1 - T1 is of higher purity than Talc - T2. Furthermore, the percentage shrinkage of the fired crisp bodies was found to increase with temperature. Pure talcs showed the lowest amount of shrinkage while body mixes having the highest percentage of clay showed the highest amount of shrinkage. In general, the percentage of water absorption of talc-clay compositions decreased as the firing temperature was increased. Mixed bodies containing Pugu clay and those containing talc1 - T1 have higher percentage of water absorption than those containing Malangali clay and talc2 - T2. This is due to the higher levels of impurities present in Malangali clays and high propotion of lime in talc2 - T2.